2017
DOI: 10.3389/fncel.2017.00254
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Degeneration after Retinal Ischemia/Reperfusion in a Rodent Model

Abstract: Retinal ischemia is a common pathomechanism in many ocular disorders such as age-related macular degeneration (AMD), diabetic retinopathy, glaucoma or retinal vascular occlusion. Several studies demonstrated that ischemia/reperfusion (I/R) leads to morphological and functional changes of different retinal cell types. However, little is known about the ischemic effects on the optic nerve. The goal of this study was to evaluate these effects. Ischemia was induced by raising the intraocular pressure (IOP) in one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 47 publications
3
46
0
Order By: Relevance
“…In macrophages, the activation of the TLR-4 signaling pathway induces an M1 polarization and inflammatory response that leads to activation of NF-κB to produce proinflammatory cytokines (IL-1β, TNF-α, iNOS, and others), which are known to play an important role in IRI, hemorrhagic shock, and retinal injury under elevated pressure ( 25 , 46 ). Various studies reported that increased expression of TNF-α seems to be related to impaired retina in cases of acutely elevated IOP ( 47 , 48 ). Except for the damage to retinal ganglion cells and optic nerve head, the elevated production of TNF-α by M1 macrophages induces a response of T-helper cells and their differentiation to Th17, which turns the acute inflammation into a fibrotic reaction ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…In macrophages, the activation of the TLR-4 signaling pathway induces an M1 polarization and inflammatory response that leads to activation of NF-κB to produce proinflammatory cytokines (IL-1β, TNF-α, iNOS, and others), which are known to play an important role in IRI, hemorrhagic shock, and retinal injury under elevated pressure ( 25 , 46 ). Various studies reported that increased expression of TNF-α seems to be related to impaired retina in cases of acutely elevated IOP ( 47 , 48 ). Except for the damage to retinal ganglion cells and optic nerve head, the elevated production of TNF-α by M1 macrophages induces a response of T-helper cells and their differentiation to Th17, which turns the acute inflammation into a fibrotic reaction ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…To induce retinal ischemia/reperfusion we used an in our group established ischemia/reperfusion model [ 11 , 50 ]. Ischemia was induced for 60 min by elevating the IOP to 140 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistological stainings were performed as previously described [ 11 , 38 , 50 , 51 , 52 ]. To prepare the retinal cross-sections ( n = 5–6/group) for immunohistochemistry, they were first dried and rehydrated in PBS, followed by blocking in 10–20% appropriate serum with 1% BSA in 0.1% or 0.2% Triton X-100 in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…There is no algorithm to define the pattern of contrast sensitivity alteration in the early stage of DR. Adachi, Jochim, and Renner. observed reduced contrast sensitivity only at single low spatial frequency in cases of non-insulin-dependent diabetes mellitus without DR [79][80][81]. Meanwhile, Joltikov et al and Safi et al reported decline in contrast sensitivity at all spatial frequencies early in the course of diabetic retinal sensory neuropathy [14,82].…”
Section: Contrast Sensitivitymentioning
confidence: 98%